Crude Oil Foulant Deposition Studies on a Heated Surface Using a Novel Batch Stirred Coupon Test Rig. (26th May 2022) - Singh, Pragya; Krishnaswamy, Srinivas; Ponnani, Krishnaswamy; Verma, Ankur; Rawat, Jaya
Abstract : The petroleum refining industry employs a wide variety of heat transfer-based equipment which tend to foul due to the complex nature of associated fluid streams and process conditions. Over the years, different test methods have been researched to understand fouling at the lab, pilot, and/or plant level. Several of these investigations have been limited to understanding fouling in static refinery streams or under non-practical operating conditions. The present study experimentally demonstrates the potential of a high-temperature batch stirred coupon test rig to characterize fouling under noncoking conditions for a specific refinery stream of interest. Experiments were conducted using a representative crude oil stream (obtained from a refinery) in a 2-liter batch autoclave system with a facility to immerse coupons attached to a rotating shaft into the stream during related test runs. The coupon Material of Construction (MOC) was chosen similar to the MOC of the tubes used in a refinery crude heat exchanger train. Experiments covered a range of bulk temperatures from 250°C to 300°C at 100 RPM. The foulant deposits obtained were found to have a strong (hard) and weakly (soft) adhering component. In the temperature range investigated, the hard and soft deposits were largely inorganic and organic in nature, respectively. The fluid bulk temperature was found to influence hard and soft deposit formation. The foulant deposits were characterized using TGA, CHNS, XRD, and SEM/EDAX, respectively. The iron and sulfur content in the hard deposit was more than 45% in total, indicating that the fouling mechanism was corrosion-based resulting from the formation of FeS on the surface. The thermal history of the soft deposit was distinct from the crude oil used. The results obtained confirm the potential of the coupon test rig for understanding fouling in refinery streams.